Synthesis of xanthohumol and xanthohumol-d3 from naringenin. Issue 46 (31st August 2021) - Andrusiak, Joanna; Mylkie, Kinga; Wysocka, Małgorzata; Ścianowski, Jacek; Wolan, Andrzej; Budny, Marcin
Abstract : A six-step synthesis of xanthohumol and its d3 -derivative from easily accessible naringenin is reported. Abstract : A six-step synthesis of xanthohumol (1a ) and its d3 -derivative (1b ) from easily accessible naringenin is reported. The prenyl side chain was introduced by Mitsunobu reaction followed by the europium-catalyzed Claisen rearrangement and base-mediated opening of chromanone gave access to an α, β-conjugated ketone system. Compound 1b was used as an internal standard in stable isotope dilution assays of 1a in two Polish beers.